Numerical modeling of population 2D-dynamics with nonlocal interaction - Aleksei Vladimirovich Borisov (Компьютерные исследования и моделирование, 2010)
Numerical solutions for the two-dimensional reaction-diffusion equation with nonlocal nonlinearity are obtained. The solutions reveal formation of dissipative structures. Structures arising from initial distributions with one and several centers of localization are considered. Formation of extending circular structures is shown. Peculiarities of formation and interaction of extending circular structures depending on nonlocal interaction are considered.